Impact of educational interventions on adverse drug events reporting - Pagotto, Caroline [UNESP]; Varallo, Fabiana; Mastroianni, Patrícia (International Journal Of Technology Assessment In Health Care, 2013)
Spontaneous adverse drug events (ADE) reporting is the main source of data for assessing the risk/benefit of drugs available in the pharmaceutical market. However, its major limitation is underreporting, which hinders and delays the signal detection by Pharmacovigilance (PhV). To identify the techniques of educational intervention (EI) for promotion of PhV by health professionals and to assess their impact. A systematic review was performed in the PUBMED, PAHO, LILACS and EMBASE databases, from November/2011 to January/2012, updated in March/2013. The strategy search included the use of health descriptors and a manual search in the references cited by selected papers. 101 articles were identified, of which 16 met the inclusion criteria. Most of these studies (10) were conducted in European hospitals and physicians were the health professionals subjected to most EI (12), these studies lasted from one month to two years. EI with multifaceted techniques raised the absolute number, the rate of reporting related to adverse drug reactions (ADR), technical defects of health technologies, and also promoted an improvement in the quality of reports, since there was increased reporting of ADR classified as serious, unexpected, related to new drugs and with high degree of causality. Multifaceted educational interventions for multidisciplinary health teams working at all healthcare levels, with sufficient duration to reach all professionals who act in the institution, including issues related to medication errors and therapeutic ineffectiveness, must be validated, with the aim of standardizing the Good Practice of PhV and improve drug safety indicators.
Keywords: Pharmacovigilance; Adverse drug reaction reporting systems; Education continuing; Educational intervention; Health knowledge; Attitudes; Practice